2013
DOI: 10.1007/s10883-013-9199-y
|View full text |Cite
|
Sign up to set email alerts
|

Exact Controllability of the Distributed System, Governed by String Equation with Memory

Abstract: We will consider exact controllability of the distributed system governed by the wave equation with memory. It will be proved that this mechanical system can be driven to the null state in finite time, the absolute value of the distributed control function being bounded. In this case the memory kernel is a linear combination of exponentials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Positive results on controllability of a one-dimensional wave equation with memory were obtained in [7]. It was shown that this equation can be driven to rest by applying a bounded distributed control.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive results on controllability of a one-dimensional wave equation with memory were obtained in [7]. It was shown that this equation can be driven to rest by applying a bounded distributed control.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is a well-known fact that this system is a basis for L 2 (Ω 0 ). We substitute ϕ = ϕ nm in (7). Then using the notation θ nm (t) = θ(t), ϕ nm we obtain…”
Section: The Orthonormalized System Of Eigenvectors Ofmentioning
confidence: 99%
“…In this case, the crochet denotes the duality pairing. Several moment problems, which are practically and historically important are formulated in this more general settings, see [56,58,87]. But, in the cases of our interest H will be a Hilbert space and…”
Section: The Goal Of This Chapter and The Moment Problemmentioning
confidence: 99%
“…This equivalence of a moment problem and an interpolation problem has been exploited for example in [40,47,48,87]. …”
Section: Moment Problems and Exact Controllabilitymentioning
confidence: 99%
“…In the literature, the controllability problems for evolution equations with memory terms have been studied extensively (See [2,15,17,21,22,25,26,28,29,30,32,33,35] and the references therein). However, in most of the existing works the problem has been addressed analyzing whether the state can be driven to zero at time t = T , without paying attention to the memory term.…”
Section: Introductionmentioning
confidence: 99%